Fabrication and quantum sensing of spin defects in silicon carbide - Luo, Qin-Yue; Li, Qiang; Wang, Jun-Feng; Guo, Pei-Jie; Lin, Wu-Xi; Zhao, Shuang; Hu, Qi-Cheng; Zhu, Zi-Qi; Xu, Jin-Shi; Li, Chuan-Feng; Guo, Guang-Can (Frontiers in Physics, 2023)
In the past decade, color centers in silicon carbide (SiC) have emerged as promising platforms for various quantum information technologies. Three main types of color centers-silicon vacancy centers, divacancy centers, and nitrogen vacancy centers in SiC-their spin states can be polarized by laser and controlled by microwave. These spin defects have been applied in quantum photonics, quantum information processing, quantum network, and quantum sensing. In this review, we first provide a brief overview of the progress in single color center fabrications for the three types of spin defects, which form the foundation of color center based quantum technology. We then discuss the achievements in various quantum sensing, such as magnetic field, electric field, temperature, strain, and pressure. Finally, we summarize the current state of fabrications and quantum sensing of spin defects in SiC and provide an outlook for future developments.